The effect of self-care counseling on health practices of adolescent pregnant women: a randomized controlled trial - Ronya Rezaie; Sakineh Mohammad-Al; Fatemeh Nemati; Mojgan Mirghafourvand (BMC, 2021)
Abstract Background Pregnancy and childbirth at an early age are associated with potential risks and complications for adolescent mothers. Health practices are behaviors that can positively affect maternal and fetal health. This study aimed to investigate the effects of self-care counseling on health practices (main outcome), attitudes towards motherhood and pregnancy, and pregnancy symptoms (secondary outcomes) in adolescent pregnant women. Methods In this randomized controlled trial, 54 adolescent pregnant women admitted to the health centers of Bukan, Iran in 2020 were enrolled. Using randomized block design, the participants were randomly assigned to the counseling (n=27) and control (n=27) groups. Those in the intervention group attended 6 self-care group counseling sessions. The Health Practices Questionnaire-II (HPQ-II), Attitudes towards Motherhood and Pregnancy Questionnaire (PRE-MAMA), and Pregnancy Symptoms Inventory (PSI) were completed before and 4 weeks after the intervention. Results Based on the results of ANCOVA with controlled baseline values, after the intervention the mean health practices score of the participants in the intervention group was significantly higher than those in the control group (adjusted mean difference (AMD): 36.34; 95% CI: 34.69 to 37.98; P<0.001). The mean attitude towards motherhood score of the participants in the intervention group was significantly higher than those in the control group (AMD: 1.01; 95% CI: 0.06 to 1.96; P= 0.038). However, the mean pregnancy symptoms score of the participants in the intervention group was partially lower than those in the control group (AMD: -1.37; 95% CI: -4.32 to 1.58; P= 0.354). Conclusion Self-care counseling sessions can improve the health practices of adolescent pregnant women and enhance their attitudes towards maternal role and pregnancy. Therefore, planners are recommended to organize self-care counseling programs for all pregnant women, especially for adolescent pregnant women. Trial registration Iranian Registry of Clinical Trials (IRCT): IRCT20120718010324N54 . Date of registration: 2/3/2020. URL: https://en.irct.ir/user/trial/42571/view ; Date of first registration: February 3, 2020.